Institutional constraints and policy choice : an exploration of local governance - Clingermayer, James C. (State University of New York Press, 2001)
Annotation Combining older institutional approaches emphasizing formal structure and governance with newer approaches and transaction cost theory, Clingermayer (political science, Northern Kentucky University) and Feiock (public administration and policy, Florida State University) argue that institutional arrangements both shape and are shaped by human behavior. They also examine contextual factors and the uncertainty of leadership in explaining how decisions are made at the level of local government. Chapters center on the institutional foundations of local governance, incentives and policy choice, constituencies, contacting, case work, leadership turnover, the delivery of services, long-term obligations, and external constraints. Annotation copyrighted by Book News Inc., Portland, OR.
Keywords: Municipal government -- United States.; Administration municipale -- États-Unis.; POLITICAL SCIENCE -- Government -- Local.; POLITICAL SCIENCE -- Government -- State & Provincial.; Municipal government; United States; Lokaal bestuur.; Besluitvorming.; Instellingen.; Verenigde Staten.